Dahsyatul Maut Fī Syi’r ‘Ḥub’ Li Adūnīs - Husnul Hamidah (University of Darussalam Gontor, 2018)
AbstractAhmed Said Asbar (Adonis) was one of the Syrian poets who invented the world's free poetry Arabic literature. Hubb from the Adonis Library on the theme